Antimicrobial and Anti-Oxidative Activities of 12-Arylbenzoacridines - Boonsong Wungsintaweekul; Kayoko Abe; Rintaro Koga; Yoshinori Katakura; Kohei Torikai (Universitas Gadjah Mada, 2020)
Searching biologically active compounds has been one of the major duties of organic chemists. We previously constructed a library of synthetic 12-arylbenzoacridines and found estrogenic and anti-estrogenic agents. With taking the shot-gun approach into consideration, further exploration for bioactive species in the above library was carried out. As a result, new antibacterial agents against S. aureus (MIC = 16 μM), E. coli (MIC = 7.8 μM), E. faecalis (MIC = 0.98 μM), and A. baumannii (MIC = 31 μM) were found. Moreover, we also unveiled that some of the tested compounds exhibit cell-based anti-oxidative activity. These results clearly show a good potential of 12-arylbenzoacridines as novel pharmacophores, which is useful to establish various medicines.